A new two‐dimensional cadmium(II) coordination polymer based on the asymmetric dicarboxylic acid homophthalic acid: synthesis, structure and properties. Issue 9 (26th August 2022) - Shen, Hong
Abstract : A cadmium(II) compound, prepared by reaction of Cd(NO3 )2 ·6H2 O with homophthalic acid and 4, 4′‐bis(2‐methylimidazol‐1‐yl)biphenyl in a mixture of H2 O and dimethylformamide, possesses a new two‐dimensional layer based on one‐dimensional [Cd(HMPH)] n chains. The compound displays a highly selective and sensitive sensing for nitrofurantoin (NFT) in aqueous solution. In addition, it displays a high photocatalytic activity for the degradation of methylene blue (MB) in water under UV‐light irradiation. Abstract : A new coordination polymer poly[[μ2 ‐4, 4′‐bis(2‐methylimidazol‐1‐yl)biphenyl‐κ 2 N 3 : N 3′ ]bis[μ3 ‐2‐(2‐carboxylatophenyl)acetato‐κ 5 O, O ′: O ′, O ′′: O ′′]dicadmium(II)], [Cd(C9 H6 O4 )(C20 H18 N4 )0.5 ] n or [Cd(HMPH)(4, 4′‐BMIBP)0.5 ] n [H2 HMPH is homophthalic acid and 4, 4′‐BMIBP is 4, 4′‐bis(2‐methylimidazol‐1‐yl)biphenyl], (I), was synthesized by the solvothermal method and was structurally characterized by means of single‐crystal X‐ray diffraction, IR spectroscopy and elemental analysis. Coordination polymer (I) exhibits a two‐dimensional layer based on one‐dimensional [Cd(HMPH)] n chains. Remarkably, photocatalytic degradation experiments on methylene blue (MB) indicated that (I) exhibits an obvious degradation effect. Moreover, an investigation of the luminescence properties of (I) revealed that it could be considered as a potential highly selective luminescence sensor for nitrofurantoin (NFT).